[March participants with reporters near Dexter lawn] (1995)
A person (possibly a reporter) is a holding a microphone to a Black march participant on the sidewalk. A person in a yellow shirt behind them has a camera slung over their shoulder, and may be a photographer associated with the possible reporter. There are several other Black and White march participants standing in the same general area. Dexter lawn, the Dexter building, and the Architecture building are visible in the background.